Food insecurity, dietary intake, and their impact on mental health among university students in Bangladesh - Marjia Sultana; Towhid Hasan; Md. Mahmudul Hasan Shohag; Nibadita Majumder; Nishat Subah Tithi; Md. Mahbub Alam (Preventive Medicine Reports)
Objective: University students, a significant demographic within the adult population, may often face increased susceptibility to psychological distress and decreased resilience, probably due to the challenges of adjusting to a new life in university. Hence, this study aimed to explore how food insecurity and dietary intake are associated with psychological distress and resilience among university students in Bangladesh. Methods: Information was collected from May to June 2024 among a sample of 450 students from Noakhali Science and Technology University, Noakhali district, Bangladesh, using a structured questionnaire assessing socio-demographic characteristics, food insecurity status, dietary intake, psychological distress, and resilience. Results: Results revealed higher level of psychological distress and lower level of resilience among university students. Regression analysis (adjusted for socio-demographics) showed a significant positive association between food insecurity and psychological distress (b = 0.437, P = 0.005); however, food consumption score was negatively associated with psychological distress (b = −0.047, P = 0.012), indicating higher levels of distress among students experiencing higher food insecurity and lower dietary intake. On the other hand, resilience was observed to be negatively associated with food insecurity (b = −0.33, P = 0.003), suggesting that students facing higher food insecurity exhibited lower resilience levels. Conclusion: The findings provided compelling evidence of the significant impact of food insecurity and dietary intake on mental health outcomes (psychological distress and resilience) among university students. Thus, addressing targeted interventions to improve university students' food insecurity and dietary intake to mitigate their psychological distress and resilience is of urgent need.